PREDICTIVE RELATIONSHIP OF NARCISSISM AND PSYCHOPATHY WITH RELATIONAL AGGRESSION MODERATED BY AGE AMONG ADOLESCENTS - Riaz, Saima; Bano, Zaqia; Ahmed, Istiaq; Naz, Iram (Journal of Ayub Medical College Abbottabad, 2021)
Background: Relational aggression stresses on the application of one’s link to interfere the someone else relationships. Narcissism is manifest by heavenliness, a feeling of being advantaged, and a nonappearance of compassion while psychopathy is a personality issue that is about reduced regret, debilitated sympathy, and critical reserved behaviours. Present study was designed to assess the predictive relationship of narcissism and psychopathy with relational aggression among adolescents moderated by age. Methods: Cross-sectional correlational research design was implied. Study was conducted at department of Psychology University of Gujrat from August 10th 2017 to 5th January 2018. 612 students from diverse academic institute of Gujrat, with age range 12-19 year were selected. Urdu version of dark triad personality scale short version was used to assess narcissism and psychopathy while diverse adolescent relational aggression scale, Urdu version was used to gauge relational aggression. Results: Multiple regression analysis was carried out to find out the combined effect of narcissism and psychopathy on relational aggression among adolescent students. Findings revealed significant predictive relation among the variables (p<0.01). Result further indicated that one unit in narcissism will increase the relational aggression by .333 unit (Î²=.333) while on unit increase in psychopathy will increase the relational aggression by .374 unit (Î²=.374). Furthermore, results support the moderating effect of age in the relation among narcissism, psychopathy and relational aggression (p<0.01). Conclusion: Narcissism and psychopathy have predictive relationship with relational aggression moreover age play moderating role in afore said association. n analysis